2012
DOI: 10.1039/c2cc16434e
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective large-scale synthesis of ZnO photocatalyst with excellent performance for dye photodegradation

Abstract: Zinc oxide with excellent photocatalytic performance for the photodegradation of dyes (superior to Degussa P25 TiO(2)) could be easily prepared in large quantity by direct calcination of zinc acetate (Zn(Ac)(2)·2H(2)O).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
205
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 547 publications
(217 citation statements)
references
References 23 publications
1
205
0
2
Order By: Relevance
“…Various semiconducting nano-photocatalysts, especially metal oxide semiconductors such as TiO 2 and ZnO, are being extensively investigated. 6,7,[17][18][19] The wide band gap of some metal oxides limits their light absorption in UV region, however, leading to less use of sunlight. 20 In order to effectively utilize sunlight, noble plasmonic nanostructured metals, such as Au, Ag, and Pt, are deposited on the surface of semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Various semiconducting nano-photocatalysts, especially metal oxide semiconductors such as TiO 2 and ZnO, are being extensively investigated. 6,7,[17][18][19] The wide band gap of some metal oxides limits their light absorption in UV region, however, leading to less use of sunlight. 20 In order to effectively utilize sunlight, noble plasmonic nanostructured metals, such as Au, Ag, and Pt, are deposited on the surface of semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various reports have shown that ZnO is one of the potential photocatalyst materials. For instances, scientists found that ZnO nanoparticles exhibit higher rate than that of TiO 2 nanoparticles (Velmurugan and Swaminathan 2011;Tian et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysis can be used as an abundant and clean energy source for different purposes like environmental remediation, clean energy production, and so forth [1][2][3]. Recent day's lot of research is going on, to develop novel photocatalyst and improve its efficiency in visible/solar light [4][5][6].…”
Section: Introductionmentioning
confidence: 99%